ANTIBIOTIC RESISTANCE CHALLENGES IN THE ICU: A CLOSER LOOK AT SARS-COV-2 TRACHEAL ASPIRATE CULTURES - Rodrigues, Ana Clara; Barros , Lucas Emilio (International Research Journal Diagnostics, 2024)
The rapid emergence and spread of the Coronavirus (SARS-CoV-2) in 2019 marked the onset of a global pandemic, posing significant health challenges. SARS-CoV-2 induces a spectrum of symptoms, ranging from coughing and fever to severe cases characterized by dyspnea and hypoxia, often leading to lung failure and fatal outcomes. This study focuses on the pandemic's impact in the state of Santa Catarina, Brazil, where the healthcare system faced a chaotic scenario, characterized by limited vaccination, high demand for ICU beds, and challenges in patient care. By October 2021, Santa Catarina reported 1,200,905 confirmed cases, with a case fatality rate of 1.62%. In the city of Lages, the study's focal point, 28,614 cases were confirmed, presenting unique healthcare challenges. Limited vaccination coverage, overwhelmed healthcare facilities, and the need for patient transfers to other towns or cities further complicated the situation. Notably, the study discusses the opening of new ICU wards in one of Lages' hospitals as a strategic response to the crisis, aiming to provide more specialized care for patients.